Pengaruh Beban Kerja dan Keseimbangan Kehidupan Kerja Terhadap Produktivitas Kerja Karyawan Pada TVRI Stasiun Sulawesi Selatan - Astika, Fifi Sri; Musa, Muh. Ichwan; Maulana, M. Ikhwan; Akbar, Abdi; Darmawan, Uhud (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2024)
This research aims to find out the influence of workload and work life balance on employee work productivity at TVRI South Sulawesi Station. The variables in this study consist of free variables, namely workload and work-life balance, and bound variables, namely employee work productivity. The population in this study is all employees of TVRI South Sulawesi Station. Sampling techniques use the Purposive sampling technique and use the slovin formula in determining the number of samples. The data collection technique used is observation and questionnaire. The data analysis technique used is multiple linear regression analysis with SPSS Software version 25 for hypothesis proof. The results of this study show that the workload has a partially significant effect on employee work productivity at TVRI South Sulawesi Station. Also, work-life balance has a partial significant effect on employee work productivity at TVRI South Sulawesi Station. Then, workload and work-life balance have a significant simultaneous impact on employee work productivity at TVRI South Sulawesi Station